2014
DOI: 10.1007/s00428-014-1675-6
|View full text |Cite
|
Sign up to set email alerts
|

Medullary carcinoma of the colon: can the undifferentiated be differentiated?

Abstract: Medullary carcinoma of the colon is a rare variant of colorectal cancer claimed to have a more favorable prognosis than conventional adenocarcinomas. The histopathologic appearance may be difficult to distinguish from poorly differentiated adenocarcinoma. The study aimed to evaluate the diagnostic interobserver agreement and to characterize the immunohistochemical and molecular differences between these two subgroups. Fifteen cases initially classified as medullary carcinoma and 30 cases of poorly differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
1
28
0
3
Order By: Relevance
“…Knox et al [4] used 90% medullary morphology as the cutoff and required the presence of MMR deficiency, and found a 2.8% prevalence. Other studies that required either any amount or undefined amount of medullary morphology [13, 23, 24] or MMR deficiency [13, 16, 23, 25] have reported prevalences ranging from <0.1% [13] to 65.7% [24]. Following the AJCC and CAP recommendation requiring > = 50% of the tumor to lack overt gland formation to diagnose poor differentiation, we regarded 50% as a reasonable cutoff in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Knox et al [4] used 90% medullary morphology as the cutoff and required the presence of MMR deficiency, and found a 2.8% prevalence. Other studies that required either any amount or undefined amount of medullary morphology [13, 23, 24] or MMR deficiency [13, 16, 23, 25] have reported prevalences ranging from <0.1% [13] to 65.7% [24]. Following the AJCC and CAP recommendation requiring > = 50% of the tumor to lack overt gland formation to diagnose poor differentiation, we regarded 50% as a reasonable cutoff in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rare medullary carcinomas in which cells create syncytial cell formations accompanied by diffuse lymphocytic infiltrates around the tumour need to be differentiated from the classic, poorly differentiated adenocarcinomas without MSI-H [21] and characterised by a poorer prognosis. Conversely, cases with mucus lakes in the tumour stroma are often misdiagnosed as classic mucinous adenocarcinoma, while in fact being mucinous carcinoma with MSI features characterised by a better prognosis, indicated by cases in the first group of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Micro satellites are repeating sequences in the human genome, and they appear because of a disorder in the mismatch repair system (MMR) that corrects replication mistakes in the DNA (3). MSI is reported to be seen in 10-15% of sporadic colorectal carcinomas, while it is seen in 100% of Lynch syndrome-associated tumors (2,3). The tumors with mutations in MMR genes are proposed to be categorized as low grade without considering histological differentiation (1).…”
Section: Case Reportmentioning
confidence: 99%
“…MC presents like conventional colonic carcinoma and can be confused with poorly differentiated colorectal carcinoma (PDC) due to undifferentiated complexion and high mitotic activity (2,3). MC of the colon is accepted as a subtype of colonic adenocarcinoma with a better clinical course and prognosis than other subtypes (1,4).There are few reports in the literature, but it has been shown that MC is frequently located at the proximal parts of the colon with low incidence of lymphnode metastases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation